Open Peer Review: Fast Forward for a New Science - Hachani, Samir (My University, 2015)
Peer review has been with humans for a long time. Its effective inception dates back to World War II resulting information overload, which imposed a quantitative and qualitative screening of publications. Peer review was beset by a number of accusations and critics largely from the biases and subjective aspects of the process including the secrecy in which the processes became standard. Advent of the Internet in the early 1990s provided a manner to open peer review up to make it more transparent, less iniquitous, and more objective. This chapter investigates whether this openness led to a more objective manner of judging scientific publications. Three sites are examined: Electronic Transactions on Artificial Intelligence (ETAI), Atmospheric Chemistry and Physics (ACP), and Faculty of 1000 (F1000). These sites practice open peer review wherein reviewers and authors and their reviews and rebuttals are available for all to see. The chapter examines the different steps taken to allow reviewers and authors to interact and how this allows for the entire community to participate. This new prepublication reviewing of papers has to some extent, alleviated the biases that were previously preponderant and, furthermore, seems to give positive results and feedback. Although recent, experiences seem to have elicited scientists’ acceptance because openness allows for a more objective and fair judgment of research and scholarship. Yet, it will undoubtedly lead to new questions which are examined in this chapter.
Keywords: Open peer review; traditional review biases; faculty of 1000